Cotipo e operadores lineares absolutamente somantes - Silva, Simeão Targino da (2010)
In this work we investigate, in detail, recent research works related to the theory of absolutely summing operators between Banach spaces. More precisely, we investigate the connection between the concept of cotype and coincidence results in the theory of absolutely summing operators.